Retinal vascular biomarkers in mild cognitive impairment and Alzheimer's disease: a comprehensive review and meta‐analysis - Sunu Mathew; Yen‐Ning Huang; Paula Bice; Andrew J. Saykin; Shannon L. Risacher (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract Retinal vasculature could be a novel, non‐invasive, and inexpensive biomarker for Alzheimer's disease (AD) ‐related neuropathology. In this comprehensive review and meta‐analysis from studies that assessed retinal vasculature using optical coherence tomography angiography in AD dementia, we calculated the pooled standardized mean differences (SMDs) in vascular density (VD)‐whole, VD‐parafoveal, vessel length density (VLD) and foveal avascular zone (FAZ) between AD and cognitively normal (CN), and between mild cognitive impairment (MCI) and CN. Thirty‐six studies were included in the meta‐analysis. The pooled SMD between AD and CN in VD‐whole, VD‐parafoveal, VLD, and FAZ was ‐0.69 (p < 0.01), ‐0.38 (p = 0.01), ‐0.59 (p < 0.01), and 0.33 (p = 0.06), respectively, and between MCI and CN in VD‐whole, VD‐parafoveal, VLD, and FAZ was ‐0.36 (p = 0.03), ‐0.17 (p = 0.44), ‐0.34 (p = 0.03), and 0.31 (p = 0.07), respectively. We identified a significant reduction in retinal vasculature in AD and MCI compared to CN. Highlights We performed a meta‐analysis of 36 studies using optical coherence tomography angiography to assess the retinal vasculature. These included 4129 participants, of which 1175 had Alzheimer's disease (AD), 1004 had mild cognitive impairment, and 1926 were cognitively normal. We identified a significant reduction in retinal vasculature in AD and mild cognitive impairment compared to cognitively normal. Retinal perfusion measured using optical coherence tomography angiography could be used as a potential biomarker for AD dementia.